ANALISIS KEMAMPUAN LAHAN BERBASIS SISTEM INFORMASI GEOGRAFIS DI DAS REJOSO BAGIAN HULU - Septiawan Billy Primadi; Kemal Wijaya; Maroeto Maroeto (JURNAL GEOGRAFI, 2022)
The research was conducted at the Rejoso watershed in the upstream part of Pasuruan Regency, East Java. This research aims to map the spread of land capabilities and land use directions in the upstream Rejoso watershed with a survey and overlay method based on Geographic Information System (SIG).The survey was conducted by observing and sampling soil on each land unit with the same characteristics as first mapping the land units resulting from the overlapping process (overlay) between slope maps, soil type maps, and land use maps on a scale of 1:50,000.The inhibitory factor of each land unit is used to classify the ability of the land which refers to the criteria of Arsyad (2010) with the matching method. Based on the results of the study, the upstream Rejoso watershed is dominated by ability class IV and VIII land with an area of 2,603.27 ha (25.84%) and 3,654.45 ha (36.27%), in addition, there is a class of land capability III with an area of 617.95 ha (6.13%), 2,137.92 ha (21.22%), and class VII land capability of 1,062.37 ha (10.54%).